2006
DOI: 10.1186/1749-799x-1-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of early arthroscopy in athletes with painful cartilage lesions of the ankle: a prospective study of 61 consecutive cases

Abstract: BackgroundAnkle sprains are common in sports and can sometimes result in a persistent pain condition.PurposePrimarily to evaluate clinical symptoms, signs, diagnostics and outcomes of surgery for symptomatic chondral injuries of the talo crural joint in athletes. Secondly, in applicable cases, to evaluate the accuracy of MRI in detecting these injuries. Type of study: Prospective consecutive series.MethodsOver around 4 years we studied 61 consecutive athletes with symptomatic chondral lesions to the talocrural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In the current study, pre-operative MRI had a sensitivity/specificity of 100/79% for chondral lesions and 50/93% for loose bodies. The herein observed sensitivity compares favorably to previous studies with reported sensitivity rates ranging from 19 to 71% [ 2 , 18 , 26 , 30 ]. This high rate could be explained either by the rather small cohort or the experience of the senior radiologist reviewing the images especially for intra-articular pathologies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the current study, pre-operative MRI had a sensitivity/specificity of 100/79% for chondral lesions and 50/93% for loose bodies. The herein observed sensitivity compares favorably to previous studies with reported sensitivity rates ranging from 19 to 71% [ 2 , 18 , 26 , 30 ]. This high rate could be explained either by the rather small cohort or the experience of the senior radiologist reviewing the images especially for intra-articular pathologies.…”
Section: Discussionsupporting
confidence: 86%
“…Magnetic resonance imaging (MRI) is often considered a non-invasive alternative to pre-operatively identify patients with intra-articular pathologies. Still, MRI has been reported to have a limited sensitivity in detecting chondral lesion and loose bodies [ 2 , 18 , 26 , 30 ]. Arthroscopy on the other hand does not only allow to reliably identify and treat intra-articular pathologies but also seems to improve the patient reported outcomes [ 23 , 34 , 35 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 One study noted an MRI accuracy of 80% in detecting osteochondral lesions in the talus and peroneus brevis tendon tears, 10 whereas another study reported a 19% detection rate of cartilage lesions found at surgery. 11 For the few studies that evaluated the lateral ankle ligamentous complex, significantly different sensitivities and specificities for detecting ATFL and CFL tears have been reported. 12 , 13 In addition, these studies had focused only on patients with chronic symptoms and injuries and there remains a paucity in the literature on the accuracy of MRI in the acute setting.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In 1996, Ferkal modified the previous classification system of Berndt and Harty with findings based on CT, listed in table 2 . 16 Instead, MRI is considered the gold standard in recognising osteochondral lesions, with 100% specificity and anywhere between 73% and 95% sensitivity. 15 …”
Section: Imagingmentioning
confidence: 99%
“…Less sensitivity, likely secondary to the thickness of imaging slices on MRI (3 mm taken in 1 mm intervals), compared with the thickness of the talar cartilage (0.4–2.1 mm), means that the false-negatives are possible, so a negative MRI with clinical symptoms requires further work-up with arthroscopy. 16 Further staging based on MRI was developed by Hepple et al , listed in table 3 . 17 …”
Section: Imagingmentioning
confidence: 99%